2010
DOI: 10.1136/thx.2010.150979.27
|View full text |Cite
|
Sign up to set email alerts
|

P76 General and respiratory health outcomes in adult survivors of bronchopulmonary dysplasia: a systematic review

Abstract: 2001e2 to 16% in 2005e6, p<0.001) for children at all treatment steps including those prescribed short acting beta agonist only. Only 27 children were prescribed LABA without concurrent ICS and of the 710 children prescribed LABA/ICS combination, 176 (25%) had not been prescribed ICS in the previous year. Conclusions Revisions of the BTS/SIGN guidelines do modify prescribing practice in children. The greater use of LABA, LTRA and reduction in ICS dose has been accompanied by a greater use of OCS that may refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 0 publications
1
63
0
Order By: Relevance
“…30,31 Systematic reviews have reported abnormal pulmonary function testing, consistent with airflow limitation in the proximal and more distal airways, among adults born preterm, as evidenced by reduced forced expiratory volume in 1 second (FEV 1 ), forced vital capacity (FVC) and forced mid-expiratory flow. 29,32 Forced expiratory volume was 0.77 standard deviations (SDs) (95% CI -0.94 to -0.60) lower in young adults who were born preterm than in those born at term, which is equivalent to a 10% decrease in predicted value. 32 Patients with BPD had even greater reductions in FEV 1 compared with those without the disease (MD -0.83 SD, 95% CI -1.01 to -0.64).…”
Section: Are We Seeing a New Pulmonary Overlapping Syndrome?mentioning
confidence: 99%
See 3 more Smart Citations
“…30,31 Systematic reviews have reported abnormal pulmonary function testing, consistent with airflow limitation in the proximal and more distal airways, among adults born preterm, as evidenced by reduced forced expiratory volume in 1 second (FEV 1 ), forced vital capacity (FVC) and forced mid-expiratory flow. 29,32 Forced expiratory volume was 0.77 standard deviations (SDs) (95% CI -0.94 to -0.60) lower in young adults who were born preterm than in those born at term, which is equivalent to a 10% decrease in predicted value. 32 Patients with BPD had even greater reductions in FEV 1 compared with those without the disease (MD -0.83 SD, 95% CI -1.01 to -0.64).…”
Section: Are We Seeing a New Pulmonary Overlapping Syndrome?mentioning
confidence: 99%
“…29 About 10% of adults who were born preterm use bronchodilators and inhaled corticosteroids, compared with 4%-6% of those born at term. 30,31 Systematic reviews have reported abnormal pulmonary function testing, consistent with airflow limitation in the proximal and more distal airways, among adults born preterm, as evidenced by reduced forced expiratory volume in 1 second (FEV 1 ), forced vital capacity (FVC) and forced mid-expiratory flow.…”
Section: Are We Seeing a New Pulmonary Overlapping Syndrome?mentioning
confidence: 99%
See 2 more Smart Citations
“…5 Much of the existing evidence focuses on adults with a history of BPD, who do have more pulmonary symptoms and respiratory function abnormalities (including obstructed airflow) than those born at term. 2,[6][7][8][9][10][11][12] Whether this outcome applies to adults born preterm at VLBW who have no history of BPD is less conclusive. Most studies may not include a sufficient number of subjects to distinguish between those with a history of BPD and those without.…”
Section: What This Study Addsmentioning
confidence: 99%